Autoantibodies to selenoprotein P in chronic fatigue syndrome suggest selenium transport impairment and acquired resistance to thyroid hormone - Sun, Qian; Oltra, Elisa; Dijck-Brouwer, D.A. Janneke; Chillon, Thilo Samson; Seemann, Petra; Asaad, Sabrina; Demircan, Kamil; Espejo-Oltra, José Andrés; Sánchez-Fito, Teresa; Martín-Martínez, Eva; Minich, Waldemar B.; Muskiet, Frits A.J.; et al. (Redox biology, 2023)
Chronic Fatigue Syndrome (CFS) presents with symptoms of hypothyroidism, including mental and physical fatigue, poor sleep, depression, and anxiety. However, thyroid hormone (TH) profiles of elevated thyrotropin and low thyroxine (T4) are not consistently observed. Recently, autoantibodies to the Se transporter SELENOP (SELENOP-aAb) have been identified in Hashimoto's thyroiditis and shown to impair selenoprotein expression. We hypothesized that SELENOP-aAb are prevalent in CFS, and associate with reduced selenoprotein expression and impaired TH deiodination. Se status and SELENOP-aAb prevalence was compared by combining European CFS patients (n = 167) and healthy controls (n = 545) from different sources. The biomarkers total Se, glutathione peroxidase (GPx3) and SELENOP showed linear correlations across the samples without reaching saturation, indicative of Se deficiency. SELENOP-aAb prevalence was 9.6–15.6% in CFS versus 0.9–2.0% in controls, depending on cut-off for positivity. The linear correlation between Se and GPx3 activity was absent in SELENOP-aAb positive patients, suggesting impaired Se supply of kidney. A subgroup of paired control (n = 119) and CSF (n = 111) patients had been characterized for TH and biochemical parameters before. Within this subgroup, SELENOP-aAb positive patients displayed particularly low deiodinase activity (SPINA-GD index), free T3 levels, total T3 to total T4 (TT3/TT4) and free T3 to free T4 (FT3/FT4) ratios. In 24 h urine, iodine concentrations were significantly lower in SELENOP-aAb positive than in SELENOP-aAb negative patients or controls (median (IQR); 43.2 (16.0) vs. 58.9 (45.2) vs. 89.0 (54.9) μg/L). The data indicate that SELENOP-aAb associate with low deiodination rate and reduced activation of TH to active T3. We conclude that a subset of CFS patients express SELENOP-aAb that disturb Se transport and reduce selenoprotein expression in target tissues. Hereby, TH activation decreases as an acquired condition not reflected by thyrotropin and T4 in blood. This hypothesis opens new diagnostic and therapeutic options for SELENOP-aAb positive CFS, but requires clinical evidence from intervention trials. [Display omitted] •Comprehensive analysis of Se and thyroid hormone in chronic fatigue syndrome.•Biomarkers of Se status, i.e., total Se, GPx3 and SELENOP correlate linearly.•Autoantibodies to SELENOP are relatively frequent in chronic fatigue syndrome.•SELENOP-aAb are associated with dysregulated GPx3 and DIO expression.•Strongly reduced urinary iodine reflects low TH activation and DIO activity.